Benomyl (Geneva, 1993)
"Evaluates the risks to human health and the environment posed by benomyl, a fungicide registered for use in 50 countries on over 70 crops, including cereals, cotton, soybeans, tobacco, mushrooms, grapes, bananas and other fruits. One of the most widely used members of the benzimidazole family of fungicides, benomyl is effective, at low usage rates, against more than 190 different fungal diseases. Because benomyl is rapidly converted to carbendazim in the environment and is extensively metabolized to carbendazim by experimental animals, data from studies of carbendazim, which is a fungicide in its own right, are also considered when evaluating the hazards of benomyl. Concerning hazards to environmental organisms, the report cites data from laboratory and field studies indicating that benomyl, applied at recommended rates, has little effect on soil microbial activity, but some adverse effects on groups of fungi. Benomyl is toxic to earthworms in laboratory experiments at realistic exposure concentrations and as a result of recommended usage in the field; earthworm populations may take more than two years to recover. Although high toxicity to aquatic organisms has been demonstrated in laboratory tests, the report concludes that this effect is unlikely to be seen in the field, due to the low bioavailability of sediment-bound residues. For the general population, the main source of potential exposure is noted to be through the ingestion of food crops containing residues of benomyl and carbendazim. Though benomyl has been shown to cause contact dermatitis and dermal sensitization in some farm workers, the report found no evidence that either of these compounds can cause systemic toxic effects in occupationally exposed subjects or the general population. The report cites findings from animal studies suggesting that both compounds pose a very low risk for acute poisoning in humans."